Heart rate variability and VO2max during a rowing training season: Implications for monitoring training adaptation - Rama, L.; Teixeira, A.; Santos, A.; Gomes, B.; Massard, A.; Rosado, F.; Alves, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In Sport Science it is generally accepted that aerobic training promotes higher Heart Rate Variability (HRV) and that intense training leads to lower HRV. The aim of this study was to analyze the utility of heart rate variability as a marker of training adaptation during a rowing training season and it`s sensibility to training load variation. Methods 9 males of the national rowing team (22,2 ±2,0 years, 181,2±7,2cm height, 77,9±8,1Kg mass) were selected for this study. HRV time domain (SDRR) and frequency domain (LF, HF absolute, relative and normalized units as was the LF/HF) were measured at rest before a graded test conducted on a Concept II rower ergometer. VO2max, was evaluated and 4 time points controlled according to a year training plan. The first evaluation (t1) took place in the begging of the training season after a transitory period during which the athletes had been released for 5/6 weeks from their normal training. This allowed us to find out the basal values at the beginning of preparation for the sport season. The second evaluation (t2) was done after the first 14 weeks of training with great aerobic predominance and a gradual increment of training volume. The third evaluation (t3) took place at the 28th week, after a phase of intensity increment and a small decrease on training volume. The final evaluation (t4) coincided with a training phase with the highest mean weekly volume and intensity during the season and before a taper period. In this study we adopted a single group repeated measures design in which athletes served as their own control subjects. All ethical presuppositions that a study of this scope compels have been verified. Results During the season, VO2max values were: t1=61,49 ± 6,21 ml.kg.min-1; t2=65,37 7,9621 ml.kg.min-1; t3=66,72 6,8021 ml.kg.min-1 and t4 =64,82 8,3021 ml.kg.min-1. The VO2 at t3 was significantly higher (p<0,05) than that observed at t1 and t4. Nevertheless the power at VO2max was from t1 to t4 respectively 334 34, 378 40, 377 52 and 387 45 Watts, higher at all moments when compared to t1 (p<0,05). Concerning HRV, we found SDRR higher at t3 (p<0,05) and lower at t4, and lower absolute HF(nu) and higher LF (nu) at t3 when compared to the initial values at t1. In summary, during the season at t3, when metabolic values of VO2max were higher, we also found the highest SDRR as marker of global variability, and the lowest LF and highest HF, which indicates a parasympathetic drive on autonomic control of the heart. Also the LF/HF shows a progressive increase during the season, although never attaining a significant variation. Conclusions Our results agree with those (1) who found a relationship between aerobic capacity development and the predominance of the parasympathetic on the sympatho-vagal balance, and confirmed the utility of at rest HRV control in monitor training adaptation on rowers during a training season.